Armington Elasticities in Intermediate Inputs Trade : A Problem in Using Multilateral Trade Data - Saito, Mika (IMF Working Papers; Working Paper ;, 2004)
This paper finds that the estimates of Armington elasticities (the elasticity of substitution between groups of products identified by country of origin) obtained from multilateral trade data can differ from those obtained from bilateral trade data. In particular, the former tends to be higher than the latter when trade consists largely of intermediate inputs. Given that the variety of intermediate inputs traded across borders is increasing rapidly, and that the effect of this increase is not adequately captured in multilateral trade data, the evidence shows that the use of multilateral trade data to estimate Armington elasticities needs caution.